Union of the European Phoniatricians' position statement on the exit strategy of phoniatric and laryngological services: staying safe and getting back to normal after the peak of coronavirus disease 2019 (issued on 25th May 2020). Issue 8 (16th August 2020) - Geneid, A; Nawka, T; Schindler, A; Oguz, H; Chrobok, V; Calcinoni, O; am Zehnhoff-Dinnesen, A; Neumann, K; Farahat, M; Abou-Elsaad, T; Moerman, M; Chavez, E; et al.
Abstract: Background: The following position statement from the Union of the European Phoniatricians, updated on 25th May 2020 (superseding the previous statement issued on 21st April 2020), contains a series of recommendations for phoniatricians and ENT surgeons who provide and/or run voice, swallowing, speech and language, or paediatric audiology services. Objectives: This material specifically aims to inform clinical practices in countries where clinics and operating theatres are reopening for elective work. It endeavours to present a current European view in relation to common procedures, many of which fall under the aegis of aerosol generating procedures. Conclusion: As evidence continues to build, some of the recommended practices will undoubtedly evolve, but it is hoped that the updated position statement will offer clinicians precepts on safe clinical practice.